Palm tocotrienol-rich fraction inhibits methionine-induced cystathionine β-synthase in rat liver - Kamisah, Yusof; Ku Zaifah, Norsidah; Ayob, Azizi; Ahmad Yusof, Asmadi; Othman, Faizah; Nonan, Mohd Rizal; Asmadi, Ahmad Yusof (Springer Netherlands, 2015)
Abstract Oxidative stress plays an important role in cardiovascular diseases. The study investigated the effects of dietary palm tocotrienol-rich fraction on homocysteine metabolism in rats fed a high-methionine diet. Forty-two male Wistar rats were randomly assigned to six groups. Five groups were fed with high-methionine diet (1 %) for 10 weeks. Groups 2 to 5 were also given dietary folate (8 mg/kg) and three doses of palm tocotrienol-rich fraction (30, 60 and 150 mg/kg) from week 6 to week 10. The last group was only given basal rat chow. High-methionine diet increased plasma homocysteine after 10 weeks, which was prevented by the supplementations of folate and high-dose palm tocotrienol-rich fraction. Hepatic S-adenosyl methionine (SAM) content was unaffected in all groups but S-adenosyl homocysteine (SAH) content was reduced in the folate group. Folate supplementation increased the SAM/SAH ratio, while in the palm tocotrienol-rich fraction groups, the ratio was lower compared with the folate. Augmented activity of hepatic cystathionine β-synthase and lipid peroxidation content by highmethionine diet was inhibited by palm tocotrienolrich fraction supplementations (moderate and high doses), but not by folate. The supplemented groups had lower hepatic lipid peroxidation than the highmethionine diet. In conclusion, palm tocotrienolrich fraction reduced high-methionine-induced hyperhomocysteinaemia possibly by reducing hepatic oxidative stress in high-methionine-fed rats. It may also exert a direct inhibitory effect on hepatic cystathionine β-synthase. Keywords Tocotrienol . Methionine . Homocysteine . S-Adenosyl methionine . S-Adenosyl homocysteine . Cystathionine β-synthase